2018
DOI: 10.1158/2326-6066.cir-17-0712
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a/β-Catenin Signaling Conditions Differentiation of Partially Exhausted T-effector Cells in Human Cancers

Abstract: In this study, we investigated the role of the Wnt/β-catenin signaling pathway in antitumor immune responses. We report that the concentration of secreted Wnt3a was significantly higher in conditioned medium from tumor or nontumor tissues obtained from all hepatocellular carcinoma or colorectal cancer patients tested, than in serum of healthy donors or patients. In addition, both Wnt3a and β-catenin were overexpressed by tumor-infiltrating and nontumor-infiltrating CD4 or CD8 T cells. The majority of these T c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Tumor growth, migration, and metastasis (43)(44)(45) Immune cell exclusion (17,27,28,(46)(47)(48) augmented DCs activation with an increased expression of costimulatory molecules and decreased expression of co-inhibitory molecules (21,22,56). Collectively, these studies show that Wnt/β-catenin signaling interferes with DC maturation and activation in the TME.…”
Section: Wnt Signaling In Tumor Cellsmentioning
confidence: 85%
See 2 more Smart Citations
“…Tumor growth, migration, and metastasis (43)(44)(45) Immune cell exclusion (17,27,28,(46)(47)(48) augmented DCs activation with an increased expression of costimulatory molecules and decreased expression of co-inhibitory molecules (21,22,56). Collectively, these studies show that Wnt/β-catenin signaling interferes with DC maturation and activation in the TME.…”
Section: Wnt Signaling In Tumor Cellsmentioning
confidence: 85%
“…Tumor DCs-deficient in LRP5/6 or β-catenin is more potent in capturing and cross-presenting TAAs to CD8 + T cells (21)(22)(23)(24) Tumor DCs lacking LRP5/6 or β-catenin are programmed to induce Th1/Th17 cells (21,22) Active Wnt/β-catenin signaling affects trafficking of DCs to tumors and TDLNs (17) Active Wnt/β-catenin signaling in tumor DCs regulates metabolic pathways involving FAO, vitamin A, and tryptophan to induce regulatory T cell (Treg) response (21)(22)(23)(24)(25)(26) Wnt-signaling in tumor DCs suppresses chemokines that are critical of recruitment and accumulation of CTL in the TME (17,27,28)…”
Section: Regulation Of DC Maturation and Activation By Wntsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CRC_S1 pathways, wnt signaling pathway was upregulated in our study. It has been reported that wnt signaling pathway contributes to tumor progression [83] and its blockade can improve the generation of effector cells [84] , thus the upregulation of wnt signaling pathway might contribute to T cell exhaustion and facilitate the growth of tumor; In the NSCLC_S1 pathways, the upregulated apoptosis may lead to the impaired function of T cells [85] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum Wnt3a expression levels in 108 samples from patients with SCCHN were quantified according to the manufacturer's instructions of the Human Protein Wnt3a ELISA kit (Cat. CSB‐EL026136HU, Cusabio Technology, Houston, TX, USA) …”
Section: Methodsmentioning
confidence: 99%